Dynamic Energy Budget model suggests feeding constraints and physiological stress in black-lip pearl oysters, 5 years post mass-mortality event. (June 2021) - Monaco, Cristián J.; Sangare, Nathanael; Le Moullac, Gilles; Basset, Caline; Belliard, Corinne; Mizuno, Keiichi; Smith, Diane L.; Lo-Yat, Alain
Abstract: Mass-mortality events of marine species can disturb the structure of communities. While identifying the causes of mass-mortality events is crucial for implementing recovery strategies, monitoring is challenging in remote locations. Black-lip pearl oysters ( Pinctada margaritifera ) are farmed for producing black pearls within remote atolls of French Polynesia. Previous mass-mortality events have resulted in the collapse of oysters and other species; however, the causes and conditions that favour recovery are unclear. We investigated the potential for oyster population recovery 5 years after a mortality event at Takaroa Atoll (Tuamotu Archipelago). Temperature, food availability (total chlorophyll- a ), growth and reproduction were monitored. Growth was also simulated using a Dynamic Energy Budget model. Despite favourable conditions, reduced growth and reproduction signalled an energetic deficit. The model overpredicted growth, and supported the hypotheses that individuals are unable to profit from the phytoplankton available and maintenance costs are high in Takaroa, ultimately explaining their poor physiological condition. Highlights: Mass-mortality events are increasingly common. Identifying the causes of mass-mortality events is challenging in remote locations. Data and an energy budget model revealed possible underlying mechanisms. Pearl oysters unable to profit from available phytoplankton after mass-mortality event Pearl oysters show high maintenance costs after mass-mortality event.